From hope to reality: a case of a syrian refugee family resettling in Canada - Zaidi, Rahat; Moura, Gustavo; Kassan, Anusha (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2024)
The increasing number of Syrian families seeking safety and security in Middle Eastern, European, and North American countries has given rise to conversations around resettlement and a timely and pertinent research theme. Through an arts-based lens reflecting on social integration post-arrival, trauma awareness, and resilience, this study follows one Syrian refugee family’s experience immigrating to Canada after living in Jordan, also as refugees. The study explores social and educational occurrences of oppression, belonging, and resilience among five family members (e.g., two parents and three children). The researchers postulate that refugee families need to adapt to a new country and meet the social expectations that often fall short of refugees’ new home’s reputation as a stable and safe place. The study informs critical refugee educational research and advocates for more situated resettlement practices in the facilitation of social integration.